The Role of User Satisfaction in Implementing a Business Intelligence System - Serumaga-Zake, Philip A.E. (South African Journal of Information Management, 2017)
Despite increasing importance of the use of Business Intelligence (BI) as a technology-driven process for giving decision support, the success or failure of BI has not been investigated fully in South Africa. BI is not well understood because of an absence of documented proof of its practice. This study was intended to investigate BI and identify the moderating and mediating effects of user satisfaction on the relationship between system quality, information quality and service quality on the one hand and perceived net benefits on the other in South Africa. Methods: The quantitative methods approach was predominantly used in this study. A total of 211 responses were obtained from a random sample of 250 BI users throughout South Africa. A semi-structured online survey questionnaire was used to collect the data, and correlation and multiple regression analyses were used to analyse it. It was found that user satisfaction mediates the relationship between perceived net benefits and system quality and service quality. It also moderates the effects of system quality and service quality on perceived net benefits. Information quality is not related with user satisfaction and perceived net benefits. The implication of the results is that system quality and user satisfaction should be enhanced and maintained to achieve perceived positive net benefits in order to make the BI system more effective and efficient.
Keywords: Business Intelligence System; Information quality; Relationship